Application of Thematic Text Tasks and Active Teaching Methods that Enable 12th Grade Students to Prepare for Writing a Reasoning Essay in Lithuanian Lessons - Stepukonienė, Inga (Pedagogika, 2015)
Students consider writing a reasoning essay as one of the most complex tasks. To perform such a task successfully one is required to have not only good knowledge of the Lithuanian literature and erudition but also creativity, one’s ability to think analytically, argumentative capacity as well as one’s mastery of the native language. Therefore, writing a reasoning essay requires not only critical thinking and an ability to express own opinion but also other important – literary and linguistic – competencies. Providing learners (12th graders) with focused thematic text comprehension tasks as well as using active methods of teaching literature to them are a theoretical prerequisite to improve their skills in writing a reasoning essay, to deepen their subject knowledge and to develop their creative skills as well as teamwork, communication, abilities and public speaking competencies. Therefore, the object of the current research is the development of working activity by applying thematic tasks of text comprehension and active methods of teaching literature in order to enable learners to prepare for writing a reasoning essay in Lithuanian lessons. The research was carried out in one of the Year 12 classes at the X gymnasium. 22 students participated in the research, ten boys and twelve girls. These were good students, active and had good relationship among each other. The qualitative measure of the chosen educational activity was the written assignments of the students. The evaluation of the essays according to their contents, expression and language usage is the fundamental criterion proving the suitability of the method. The students were also offered to evaluate the acquired abilities themselves by writing a half-structured learning process and result reflection. Having carried out the empirical research showed that applying focused thematic text comprehension tasks and active methods of teaching literature in literature classes helped the learners to prepare better for writing a reasoning essay. The presentation of thematic text comprehension tasks has improved the learners’ competencies in subject matter and comprehension, argumentation, statement grounding and paragraph writing according to the set criteria. The active methods have created an opportunity for learners to improve the knowledge of literary theory and history as well as text analysis and interpretation. The methods have also deepened the learners’ skills and abilities in information selection and systematization and public speaking. Individual and group work has enabled the students to uncover the “great discoveries” themselves. The students have become more independent, more creative, more motivated, developed broader literary understanding and could therefore describe in more precise detail the studied literary and cultural phenomena and processes and that has allowed them to achieve better results in creative writing.